Parallel Control of Auxiliary Inverters for High-Speed EMU - WEI Kai; ZHANG Zhixue; SHANG Jing (Kongzhi Yu Xinxi Jishu)
The control strategy of parallel inverters was analyzed and implemented with the background of high-speed EMU program. By calculating positive power and negative power, output voltage and frequency of auxiliary inverters were controlled with the PQ droop method to implement auxiliary inverters in parallel with no control interconnection. Result of the full-power ground combination experiment to highspeed EMU parallel inverters show that the parallel system has stable operation, fast transient response and good current-sharing.